2012
DOI: 10.5999/aps.2012.39.5.504
|View full text |Cite
|
Sign up to set email alerts
|

Does Fibrin Sealant Reduce Seroma after Immediate Breast Reconstruction Utilizing a Latissimus Dorsi Myocutaneous Flap?

Abstract: BackgroundThe most common complication of latissimus dorsi myocutaneous flap in breast reconstruction is seroma formation in the back. Many clinical studies have shown that fibrin sealant reduces seroma formation. We investigated any statistically significant differences in postoperative drainage and seroma formation when utilizing the fibrin sealant on the site of the latissimus dorsi myocutaneous flap harvested for immediate breast reconstruction after skin-sparing partial mastectomy.MethodsA total of 46 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…For example, Cha et al who applied it in immediate breast reconstruction utilizing a latissimus dorsi myocutaneous flap. 10 Burak et al whose results using only bovine thrombin failed to get significant outcome, similar results obtained by Cipolla et al in their study over 159 patients. 18, 30 Vaxman et al reported that with the use the fibrin glue the total drain output increased.…”
Section: The Statistical Analysis Of Received Pre-and Postoperative Dsupporting
confidence: 74%
See 1 more Smart Citation
“…For example, Cha et al who applied it in immediate breast reconstruction utilizing a latissimus dorsi myocutaneous flap. 10 Burak et al whose results using only bovine thrombin failed to get significant outcome, similar results obtained by Cipolla et al in their study over 159 patients. 18, 30 Vaxman et al reported that with the use the fibrin glue the total drain output increased.…”
Section: The Statistical Analysis Of Received Pre-and Postoperative Dsupporting
confidence: 74%
“…Its role in seroma prevention has been studied with varying results in mastectomy and thyroidectomy patients. [9][10] Human fibrin glue (HFG) is formed of two components contained in separate vials; the first component is a freeze-dried concentrate of clotting proteins, mainly fibrinogen, Factor XIII and fibronectin (the sealant) and the second substance is freeze dried thrombin (the catalyst). The first component is reconstituted with an aprotinin solution that inhibits tissue fibrinolysis.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we did not observe a statistically significant difference in the drain removal time, so we inferred that FS did not reduce the drainage amount, as the adhesive sealant blocked the lymphatic channel in both the early and the late phase. This might be attributed to the re-opening of the lymphatic system after surgery, irrespective of the use of FS [12,18].…”
Section: Discussionmentioning
confidence: 99%
“…First, we think that the area of the back donor site is too large to be covered with only 4 mL of FS; further, it is difficult to predict which part will have reactive fluids or bleeding when applying FS. Second, since reactive fluid formation occurs frequently in the back area and leads to a drainage amount of tens of milliliters a day, it is difficult for FS to have a distinct adhesive effect [18]. Third, as the constant movement of the patient's shoulder and flank area generates a shearing effect between the skin and the underlying musculature, it is difficult to have the same effect as that of an FS application to a small area such as an internal organ or a vessel that has minimal movement.…”
Section: Discussionmentioning
confidence: 99%
“…When drainage was less than 20 mL for a 24-hour period, the drainage tubes were removed. 13,14 Outcome of the measures was the volume of drainage output, the length of time that the drain remained in the site, hospitalization period, and evaluation of dead space using ultrasonography. In addition, any complications, including recurred seroma, wound dehiscence, infections, and delayed wound healing, were studied.…”
Section: Methodsmentioning
confidence: 99%